An Analysis of Rohingya Conflict in Myanmar through Ted Gurr’s "Why Men Rebel." - Albela, Emmanuel Jeric (HISTORICAL: Journal of History and Social Sciences, 2024)
This study is an analysis of the background and history of Rohingya Conflict in Myanmar. It tries to reveal the root causes of the conflict as well as the other factors that made this conflict lasted until today. The researcher will use the historical method by operating the descriptive-narrative-analytical techniques to bring out the major key points of the research. With the incorporation of Ted Gurr’s “Why Men Rebel” Theory of Revolution, the researcher would like to bring the discussion on how this seven-decade conflict in Myanmar’s history affected its image in the international politics. Here, the researcher will try to look into the “relative deprivation” stressed by Gurr, placing it on the side of the Rohingya people as they have been deprived not only of citizenship by the government of Myanmar, but also of territory and other elements for them to live peacefully. It led to several violent encounters between the Rohingya people and the forces of the government of Myanmar. Hence, the researcher would like to put the Rohingya case on Gurr’s claim: "as frustration produces aggressive behavior on the part of an individual, so too does relative deprivation predict collective violence by social groups." In this case, the government of Myanmar’s deprivation of many aspects from this minority ethnic group from Rakhine State, resulted in aggression that led to several violent encounters with the government throughout the years.